Killing strangers how political violence became modern - Wilson, Timothy Keith 1971- (Oxford University Press, 2020)
A bewildering feature of so much contemporary political violence is its stunning impersonality, with every city centre a potential shooting gallery; every metro system a potential bomb alley. Killing Strangers explores how acts of political violence have changed over time, becoming 'unchained' from inter-personal relationships
Literaturverzeichnis Seite [217]-246
Keywords: Terrorism / History; Political violence / Social aspects; Politik; Radikalismus; Gewalt; Terrorismus